The durability of superhydrophobic and slippery liquid infused porous surface coatings under corona discharge characteristic of the operation of high voltage power transmission lines - Kirill A. Emelyanenko; Alexander G. Domantovsky; Pavel S. Platonov; Pavel S. Kochenkov; Alexandre M. Emelyanenko; Ludmila B. Boinovich (Energy Reports, 2022)
Application of polyfunctional water-repelling coatings for high voltage outdoor power lines wires, insulators, and line supports recently gathered large interest due to their ability to substantially boost performance. Such functionalization can mitigate the accumulation of water precipitates and atmospheric pollutions, decrease leakage current, increase flashover and corona ignition voltage. However, harsh conditions concomitant to a high voltage such as high energy ions and electrons, high ozone concentration, UV radiation impose strict requirements on the durability of applied coatings. In this paper, we focus on the analysis of the durability of superhydrophobic coatings (SHC) and slippery liquid infused porous surfaces (SLIPS) under prolonged exposure to industrial grade alternating current corona discharge. Reported results show that in contrast to previously reported low resilience of polymer-based SHC, proper metal-based SHC withstands many hours of exposure without notable degradation. The obtained data on the stability of SLIPS under corona discharge show notable degradation related to the high rate of infused layer depletion. Overall, reported results broaden the understanding of the effect of corona exposure on functional materials and reinforce the optimistic view on the applicability of SHC and SLIPS coatings in the power transmission industry.